2019
DOI: 10.1186/s40949-019-0024-7
|View full text |Cite
|
Sign up to set email alerts
|

Learning from studying very rare cardiac conditions: the example of short QT syndrome

Abstract: Background: Some congenital heart conditions are very rare. In a climate of limited resources, a viewpoint could be advanced that identifying diagnostic criteria for such conditions and, through empiricism, effective treatments should suffice and that extensive mechanistic research is unnecessary. Taking the rare but dangerous short QT syndrome (SQTS) as an example, this article makes the case for the imperative to study such rare conditions, highlighting that this yields substantial and sometimes unanticipate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 144 publications
(286 reference statements)
0
9
0
Order By: Relevance
“…Additionally, the deactivation kinetics of the channel allow I Kr to influence diastolic depolarization of cardiac pacemaker cells (Ono and Ito, 1995;Mitcheson and Hancox, 1999). Inherited mutations in hERG that attenuate inactivation ("gain of function") result in premature repolarization and shortening of the QT interval (short QT syndrome; SQTS) (Campuzano et al, 2019;Hancox et al, 2019). Loss of function mutations, many (but not all) of which arise from disrupted trafficking of hERG to the cell surface (Anderson et al, 2014), can result in inefficient repolarization and thus an elongation of the QT interval (long QT syndrome; LQTS).…”
Section: The Significance Of the Herg Potassium Channelmentioning
confidence: 99%
“…Additionally, the deactivation kinetics of the channel allow I Kr to influence diastolic depolarization of cardiac pacemaker cells (Ono and Ito, 1995;Mitcheson and Hancox, 1999). Inherited mutations in hERG that attenuate inactivation ("gain of function") result in premature repolarization and shortening of the QT interval (short QT syndrome; SQTS) (Campuzano et al, 2019;Hancox et al, 2019). Loss of function mutations, many (but not all) of which arise from disrupted trafficking of hERG to the cell surface (Anderson et al, 2014), can result in inefficient repolarization and thus an elongation of the QT interval (long QT syndrome; LQTS).…”
Section: The Significance Of the Herg Potassium Channelmentioning
confidence: 99%
“…On the other hand, our simulation results clearly suggested that the S755T mutation resulted in a marked decrease in the minimal substrate size required for initiating and maintaining reentry arrhythmias. This highlights that both temporal and spatial vulnerability need to be evaluated to avoid biased conclusions and to understand the overall effects by mutations [31]. In the case of SQTS6, the increased spatial vulnerability in the mutation condition dominated, and eventually contributed to higher risks of developing arrhythmias in SQTS patients.…”
Section: Discussionmentioning
confidence: 99%
“…A list of genes and associated mutations that have been linked to congenital SQTS. (The table is modified from [13] and [17], with additional mutations reported in [27][28][29][30]. ♂, inherited from father; ♀, inherited from mother; * truncation mutant.…”
Section: The Sqt1 Variant and Mutations To Hergmentioning
confidence: 99%